Five-year performance analysis of a cystic fibrosis newborn screening program in northeastern Brazil - Carolina Godoy; Danielle C. Paixão; Ney C.A. Boa-Sorte; Tatiana Amorim; Luiz Vicente R.F. da Silva Filho; Edna Lúcia Souza (Elsevier, 2023)
Objective: To analyze the performance of the cystic fibrosis (CF) newborn screening (NBS) program over its first five years in a Brazilian northeastern state. Method: A population-based study using a screening algorithm based on immunoreactive trypsinogen (IRT)/IRT. Data were retrieved from the state referral screening center registry. The program performance was evaluated using descriptive indicators such as the results of an active search, coverage, newborn's age at the time of blood sampling, the time between sample collection and its arrival at the laboratory, and the child's age at diagnosis of disease. Results: The public CF screening program covered 82.6% of the 1,017,576 births that occurred, with an accumulated five-year incidence of 1:20,767 live births. The median (25th-75th) age at diagnosis was 3.5 (2.3-7.3) months. The sampling before 7 days of life for the first IRT (IRT1) increased between 2013 and 2017 from 42.2 to 48.3%. Around 5% of IRT1 samples and 30% of the second samples were collected after 30 days of life. In the first and second stages of screening, 23.6% and 19.9% of the infants, respectively, were lost to follow-up. In both stages of screening, the samples were retained at the health units for a median (25th-75th) of 9.0 (7.0-13.0) days. Conclusions: The coverage by the CF-NBS program was satisfactory as compared to other Brazilian state rates and the percentage of IRT1 samples collected within the first week of life increased progressively. However, time of samples retention at the health units, inappropriate sampling, inherent methodological problems, and loss of follow-up need to improve.